2015
DOI: 10.1021/jacs.5b05376
|View full text |Cite
|
Sign up to set email alerts
|

Selective Radical–Radical Cross-Couplings: Design of a Formal β-Mannich Reaction

Abstract: A direct β-coupling of cyclic ketones with imines has been accomplished via the synergistic combination of photoredox catalysis and organocatalysis. Transient β-enaminyl radicals derived from ketones via enamine and oxidative photoredox catalysis readily combine with persistent α-amino radicals in a highly selective hetero radical–radical coupling. This novel pathway to γ-aminoketones is predicated upon the use of DABCO as both a base and an electron transfer agent. This protocol also formally allows for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
130
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(136 citation statements)
references
References 43 publications
2
130
0
4
Order By: Relevance
“…53,54 In addition, we have demonstrated that nucleophilic radical 22 can be trapped by closed-shell electrophiles, such as Michael acceptors, to generate β-alkylated aldehydes in good yield. 55 During the development of these transformations, the use of DABCO as base was identified as key for achieving high efficiencies.…”
Section: Dual Photoredox Organocatalysis: Covalent Activation Modesmentioning
confidence: 94%
See 1 more Smart Citation
“…53,54 In addition, we have demonstrated that nucleophilic radical 22 can be trapped by closed-shell electrophiles, such as Michael acceptors, to generate β-alkylated aldehydes in good yield. 55 During the development of these transformations, the use of DABCO as base was identified as key for achieving high efficiencies.…”
Section: Dual Photoredox Organocatalysis: Covalent Activation Modesmentioning
confidence: 94%
“…Challenging carbon–carbon bond-forming reactions between sterically congested C(sp 3 )–centers can also be achieved using radical–radical coupling platforms. 51,53,54 Indeed, the recent catalytic strategy outlined by Ooi 56 raises the exciting prospect of a general and enantioselective approach to these sterically encumbered systems.…”
Section: Dual Photoredox Organocatalysis: Noncovalent Interactionsmentioning
confidence: 99%
“…reported that in analogy to γ -hydroxyketones, racemic γ -aminoketones can be synthesized via coupling of β -enaminyl radicals with α -amino radicals under photoredox conditions with Ir III (ppy) 2 (dtbbpy)PF 6 catalyst. 63 The reaction is applicable to a wide range of imine coupling partners: aldimines, diaryl and aryl-alkyl ketimines furnish the desired γ -aminoketones in high yields (Scheme 16). With regard to the β -enaminyl radical precursors, cyclohexanone derivatives with substituents at 2-, 3-, and 4-positions as well as cyclopentanones readily undergo the β -aminoalkyl ketone-forming reaction.…”
Section: Radical-radical Coupling Reactionsmentioning
confidence: 99%
“…Since Ru II (bpy) 3 Cl 2 was first reported to engage in a SET with aromatic carbonyl compounds in the late 1970s, 44 visible light organometallic photoredox catalysis has become widely recognized as an efficient way to generate ketyl 45-62 and α -aminoalkyl anion radicals under mild reaction conditions. 58, 63-65 …”
Section: Introductionmentioning
confidence: 99%
“…Since their initial success in direct β -activation, the MacMillan group have added three examples to this "β -carbon radical" strategy that involved direct β -alkylation of saturated carbonyl compounds with aryl ketones (Scheme 19a), 73 Michael acceptors (Scheme 19b), 74 and imines (Scheme 19c) 75 to produce a wide variety of β -functionalized products.…”
mentioning
confidence: 99%